Adsorption on Toxic Metal Pb(II), Cd(II), Hg(II) and Cu(II) Ions on Agricultural Byproducts - Meshram, Y.K. (Asian Journal of Chemistry, 2016)
Agricultural byproducts like orange, banana, pomegranate, apple, chickoo, sweetlime were used in their natural state on which the study of adsorption of toxic metal ions Pb(II), Cd(II), Hg(II) and Cu(II) at 27°C has been made. The values of Freundlich constants (n and k) are estimated from the study. It can be seen that adsorption increases with the increase in concentration of metal ions.